2016
DOI: 10.1542/peds.2014-3761
|View full text |Cite|
|
Sign up to set email alerts
|

Diabetic Striatopathy in Childhood: A Case Report

Abstract: Diabetic striatopathy is a well-known complication of diabetes in adults. To our knowledge, only 2 cases have been reported in children. We here report the case of a teenager in whom diabetic striatopathy was revealed by the subacute appearance of hemichorea-hemiballism in the context of weight loss, polyuria, and polydipsia. Glycemia control allowed rapid clinical recovery despite established striatal lesions documented on MRI. We also discuss current hypotheses about pathophysiological processes underlying t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 8 publications
0
17
0
1
Order By: Relevance
“…In those cases along with weight loss, polyuria, and polydipsia was reported hemichorea-hemiballism that was receded after glucose control 27 . Among others taking right clinical history of a patient and not only the lean on the lab results for diabetic patients is quite important.…”
Section: Complications Of Diabetes Mellitusmentioning
confidence: 99%
“…In those cases along with weight loss, polyuria, and polydipsia was reported hemichorea-hemiballism that was receded after glucose control 27 . Among others taking right clinical history of a patient and not only the lean on the lab results for diabetic patients is quite important.…”
Section: Complications Of Diabetes Mellitusmentioning
confidence: 99%
“…Nonketotic hyperglycemic chorea-ballism (NKHCB) has been well described in older Asian females [1][2][3][4] and rarely in children. 5,6 There were six previous case reports involving children and adolescents (►Table 2). 2,5,[7][8][9][10] The cases were predominantly in adolescents with abnormalities on imaging studies.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 There were six previous case reports involving children and adolescents (►Table 2). 2,5,[7][8][9][10] The cases were predominantly in adolescents with abnormalities on imaging studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Das et al reported the occurence of Ds in two young males with diabetic ketoacidosis. There have been only a few cases of Ds so far in children, including one in a teenager with subacute onset of hemichorea accompanied by weight loss, polydipsia and polyuria [10].…”
Section: Biopsy -Histopathologymentioning
confidence: 99%